2019
DOI: 10.1111/1471-0528.15872
|View full text |Cite
|
Sign up to set email alerts
|

Negligible risk of prenatal ductus arteriosus closure or fetal renal impairment after third‐trimester paracetamol use: evaluation of the German Embryotox cohort

Abstract: A recent case series evaluated a potential link between paracetamol use during pregnancy and premature constriction or closure of the fetal ductus arteriosus (Allegaert et al. Br J Clin Pharmacol 2019;85:245-51). Criteria from the World Health Organization Uppsala Monitoring Centre causality assessment tool were applied, and in 15 of 25 cases, causality was classified as probable or certain, with another nine cases classified as possible. How should this information be interpreted clinically given that there … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 29 publications
0
12
0
Order By: Relevance
“…Patients who used acetaminophen in the third trimester of pregnancy (n¼604) showed no increased risk of premature closure of the DA compared with those who had only used it within only the first two trimesters of pregnancy (n¼1192), a control group selected to control for medical comorbidities that are the reason for analgesic use in pregnancy. 19 In this study, frequent or daily use in the third trimester of pregnancy was only recorded in 31 of 604 patients (5.1%), with most patients only using acetaminophen for a short term of 7 days (364 of 604 patients [60.3%]) and an unspecified number of exposure days in 154 of 604 patients (25.5%). The median last exposure to acetaminophen was 35 3/7 weeks' gestation (range, 32 0/7e38 4/ 7 weeks' gestation).…”
Section: Published Studies and Case Reportsmentioning
confidence: 59%
See 3 more Smart Citations
“…Patients who used acetaminophen in the third trimester of pregnancy (n¼604) showed no increased risk of premature closure of the DA compared with those who had only used it within only the first two trimesters of pregnancy (n¼1192), a control group selected to control for medical comorbidities that are the reason for analgesic use in pregnancy. 19 In this study, frequent or daily use in the third trimester of pregnancy was only recorded in 31 of 604 patients (5.1%), with most patients only using acetaminophen for a short term of 7 days (364 of 604 patients [60.3%]) and an unspecified number of exposure days in 154 of 604 patients (25.5%). The median last exposure to acetaminophen was 35 3/7 weeks' gestation (range, 32 0/7e38 4/ 7 weeks' gestation).…”
Section: Published Studies and Case Reportsmentioning
confidence: 59%
“…The only published study reporting a control group in a retrospective cohort did not find an association. 19 Appraisal of the pharmacokinetic and pharmacodynamic literature also supports that premature closure of the DA is an unlikely effect associated with prenatal acetaminophen use. Pharmacokinetic studies found that fetal levels are approximated from maternal levels, which range from 4.5 to 12.3 mg/L.…”
Section: Expert Reviewmentioning
confidence: 94%
See 2 more Smart Citations
“…Furthermore, paracetamol also became one of the drugs used to treat (symptomatic) patent ductus arteriosus in preterm neonates [10]. Also, the association between maternal paracetamol use and fetal ductus arteriosus constriction or closure has more recently been reported, although this risk is difficult to quantify and is likely very low [11,12].…”
Section: Introductionmentioning
confidence: 99%